Предмет: Алгебра,
автор: polinashilova1
Разложи на множители: 36t^2−(t−p)^2 Помогите!!!
Ответы
Автор ответа:
0
36t²−(t−p)²= (6t)²−(t−p)²=(6t−t+p)(6t+t-p)=(5t+p)(7t-p)
Автор ответа:
0
36t²-(t-p)² =
(6t-(t-p))(6t+(t-p)) =
(6t-t+p)(6t+t-p) =
(5t+p)(7t-p).
Ответ: (5t+p)(7t-p).
(6t-(t-p))(6t+(t-p)) =
(6t-t+p)(6t+t-p) =
(5t+p)(7t-p).
Ответ: (5t+p)(7t-p).
Похожие вопросы
Предмет: Экономика,
автор: mbolshakova11
Предмет: Алгебра,
автор: txdtxtxxyfufgihii
Предмет: Биология,
автор: Аноним
Предмет: Информатика,
автор: илья12451245
Предмет: Математика,
автор: Оксаночка111